2013
DOI: 10.1186/1471-2253-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remifentanil infusion rate on stress response in orthopedic surgery using a tourniquet application

Abstract: BackgroundCurrently, in the field of general anesthesia, balanced anesthesia in combination with analgesic, hypnotic, and muscle relaxant is commonly used. Remifentanil is the standard analgesic used in balanced anesthesia, and has contributed greatly to reduce the physical stress of the patient during surgery. We compared the stress response suppression effect of remifentanil by measuring stress hormones in 2 groups treated with different analgesic doses in orthopedic surgery using a tourniquet.MethodsTwenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…These changes persist until tourniquet deflation and poorly respond to analgesic drugs or increasing the depth of anesthesia. Many interventions have been reported to reduce cardiovascular stress:[242526272829303132] Ketamine, dexmedetomidine, magnesium sulfate, clonidine, and remifentanil infusion.…”
Section: Systemic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes persist until tourniquet deflation and poorly respond to analgesic drugs or increasing the depth of anesthesia. Many interventions have been reported to reduce cardiovascular stress:[242526272829303132] Ketamine, dexmedetomidine, magnesium sulfate, clonidine, and remifentanil infusion.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…Many techniques[27] like application of EMLA cream, infiltration with local anesthetics, use of wider cuff with lower inflation pressure, addition of opioids, clonidine, epinephrine along with local anesthetics in spinal block have been tried in order to decrease the incidence or severity of this pain but none has attained complete success in pain relief. Intravenous drugs,[242527282930313247] ketamine, dexmedetomidine, magnesium sulfate, clonidine remifentanil infusions have also been studied, and the only thing that works reliably is tourniquet deflation.…”
Section: Tourniquet Painmentioning
confidence: 99%
“…Previous studies have shown that anaesthetic drugs, more specifically the hypnotic etomidate, can suppress adrenocortical synthesis of cortisol . However, many other drugs may have HPA suppressive properties as suggested by small interventional studies in surgical and ICU patients, by observational studies of surgical patients and by animal experiments. Based on the available evidence, we hypothesized that the pharmacological effects of drugs used during surgery or the acute phase of critical illness prior to ICU admission may explain the acute ‘ACTH‐cortisol dissociation’, as observed upon admission to the ICU.…”
Section: Introductionmentioning
confidence: 97%
“…In most previous studies examining the effects of intraoperative glucose administration on metabolism, general anaesthesia was maintained with fentanyl without remifentanil and the type of surgery varied. Generally speaking, remifentanil is more useful for controlling intraoperative stress [13,14]. In addition, the anaesthetic drug that was used Figure 5.…”
Section: Figurementioning
confidence: 99%
“…In addition, the glucose levels of the subjects in these previous studies might have been relatively high because the general anaesthesia was maintained with fentanyl instead of remifentanil, which is better at preventing hyperglycaemia as it can effectively control intraoperative stress [13,14]. Furthermore, the types of surgery performed varied between the studies, with differences in the invasiveness of the procedures and, hence, in the extent of the intraoperative stress that was induced.…”
Section: Introductionmentioning
confidence: 99%